Women in the management of higher education: illness and strategies to cope with the work demands - Trebien, Valicir Melchiors; Trindade, Letícia de Lima; Amestoy, Simone Coelho; Corralo, Vanessa; Zocche, Denise Azambuja; Bordignon, Maiara (Saúde e Sociedade, 2021)
This article aims to investigate illness and coping strategies for suffering at work among women in higher education management. This is a qualitative and quantitative case study conducted with 34 women. A sociodemographic questionnaire and the Pleasure and Suffering at Work Indicator Scale were applied to all participants, and an interview was conducted with seven of them. Quantitative data underwent statistical analysis and qualitative data underwent content analysis, being discussed in the light of the Psychodynamics of Work. The results show that 52.9% of the women presented with symptomatic manifestations or health problems, which they considered as work-related. The coping strategies adopted for work demands were mostly individual, including psychotherapy, medication, integrative therapies, spiritual and physical activities, as well as rest breaks. They also reported some collective coping strategies, such as meeting and talking to colleagues, friends, and family. Thus, authorities must develop institutional strategies to reduce occupational suffering, prevent illness, and promote work pleasure.